Entrepreneurial orientation and effectiveness of small and medium agro-based enterprises (SMAES) in Malaysia – mediating effect of knowledge and network strategies / Amran Awang, Zainal Ariffin Ahmad and Abdul Rashid Said Asghar - Awang, Amran; Ahmad, Zainal Ariffin; Said Asghar, Abdul Rashid (Universiti Teknologi MARA Cawangan Pahang, 2007)
This paper aims to explore the mediating role of knowledge andnetworking on entrepreneurial orientation (EO)-performance relationship among the small and medium agro-based enterprises (SMAEs) in Malaysia. The concept is somewhat vague thus knowledge-base and networking strategies are some basic features to understand in the relationships. EO, knowledge and network were entrepreneurial capabilities under the purview of the resource-based view (RBV) that were found to explain firm’s effectiveness. Results of the study noted that EO dimensions among SMAEs entrepreneurs showed strong relationship to knowledge-base elements of human capital development and tacit knowledge and network variables (consist of strategic alliance and social network capabilities). The analysis done to 615 Malaysian agro-based small business entities (SMAEs) discovered social network as mediator in the EO’s competitiveness-effectiveness relationship. The results imply that Malaysian SMAEs consider social networking as an efficient means of entrepreneurial firms to be more effective. The study encapsulates proposed future research directions.